Efektivitas dan Kontribusi Surat Berharga Negara terhadap Pembiayaan Defisit Anggaran Pendapatan dan Belanja Negara di Indonesia Tahun 2012 – 2021 - Laras Lapita Sari; Marselina Marselina (Journal on Education, 2023)
This study aims to identify the effectiveness and contribution of Government Securities (SBN) to financing the State Revenue and Expenditure Budget (APBN) deficit in Indonesia from 2012-2021. The research method used is a quantitative approach using secondary data, and the research is descriptive. The analysis was carried out by calculating the percentage of effectiveness and contribution of SBN consisting of Government Debt Securities (SUN) and Government Sharia Securities (SBSN) both domestic and foreign currency in covering the APBN deficit. The research results show that on average SBN during the 2012-2021 period was effective and contributed significantly to financing the APBN deficit. Secondary data analyzed includes the issuance, target and realization of SBN, as well as the size of the APBN deficit during that period. This research provides an overview of the important role of SBN in supporting the fiscal stability of the Indonesian government.